Improving the Quality of Total Hip Arthroplasty Operative Notes: A Clinical Audit Study - Rajeev Shukla; Devendra Nayak; Anurag Jain; Arpit Choyal; Aayush Kumar Soni (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: A very important part of good medical practice is to maintain patient records. Accurate and detailed operation notes are of great importance in all surgical specialties, not only for patient care but also for providing information for research, audit, and medico-legal purposes. Operative notes are often presented in legal malpractice cases, and most of them are indefensible from a medico-legal standpoint. Incomplete and illegible notes are often a source of weakness in the defense of surgeons in courts. Clear and legible notes relating to all surgical procedures are therefore extremely important. In this study, we assess the quality of operative notes against the standards set by the Royal College of Surgeons of England with a view to improving the quality of operative notes and ensuring quality patient care. Materials and Methods: This study was conducted in a tertiary care hospital in central India. A sample size of 47 orthopedics arthroplasty operation notes was collected between March 2021 and October 2021 from the Department of Orthopaedics at SAMC and PGI, Indore, and they were retrospectively audited by senior orthopedics surgeons according to the Royal College of Surgeons of England Good Surgical Practices Guidelines. The notes were audited keeping in mind the guidelines set by the Royal College of Surgeons of England Good Surgical Practice with some additional points which was related to hip arthroplasty making up 21 points which is described in table below. Results: During the audit cycle, 47 operation notes of hip arthroplasty surgeries performed between March 2021 and October 2021, were retrospectively reviewed against the guidelines for the operation notes set by the Royal College of Surgeons of England in the recent 2014 edition; there was good compliance with respect to date documentation (85%), diagnosis (97%), name of operating surgeon (95%), assistants’ names (89%), description of the operative procedure (70%), detailed postoperative instructions (100%) and the signature (96%), name of responsible consultant (93%), details of the serial number of prosthetic used (98%). The audit highlighted two components with poor compliance: description of other procedures performed such as catheterization/calf stimulators/foot pumps (67%), details of suture used (69%). A memory aid was then designed and placed in the operation room for two months, emphasizing the poorly documented aspects. Conclusion: The format used in our hospital SAMC and PGI aligns well with the criteria described by the Royal College of Surgeons Good Surgical Practice guidelines released in 2014. Our installation of memory aid in the operation theater improved the stats of some of the criteria; however, some points in the operation notes still remain poorly filled in. We strongly recommend continuing with the implementation of audits in our clinical practice among resident doctors and consultant surgeons of the departments in order to closely analyze our practices, especially with regard to patient safety and quality of care.